Dietary Probiotic Supplementation Suppresses Subclinical Necrotic Enteritis in Broiler Chickens in a Microbiota-Dependent Manner - Zhao, Ying; Zeng, Yan; Zeng, Dong; Wang, Hesong; Sun, Ning; Xin, Jinge; Zhou, Mengjia; Yang, Hanbo; Lei, Lei; Ling, Hongli; Khalique, Abdul; Rajput, Danish Sharafat; et al. (Frontiers in Immunology, 2022)
Background Chicken meat is one of the most consumed meats worldwide and poultry production is increasing at an exponential rate. Reducing antibiotic usage has resulted in the recurrence of subclinical necrotic enteritis again and influenced global poultry production. Probiotics are potential antibiotic substitutes that can be used to prevent subclinical necrotic enteriti. However, the precise mechanism of action of probiotics and information on which gut microbes confer this efficacy remain elusive. Methods and results The subclinical necrotic enteritis animal model was used to reveal the mechanism underlying the effect of probiotics on intestinal health through RNA sequencing and 16S rDNA amplicon sequencing. Bacillus licheniformis H2 feeding significantly reduced the relative abundance of Clostridium perfringens in the ileum and markedly ameliorated the pathological damage in the ileum and liver. In addition, oral administration of B. licheniformis H2 contributed to the enhancement of the intestinal barrier function and epithelial renewal, reducing energy consumption, and improving enteral nutrition absorption. Probiotic B. licheniformis H2 also ameliorated the inflammatory response and increased the immunity of subclinical necrotic enteritis infected broilers. Finally, B. licheniformis H2 feeding regulated liver gene expression to suppress immune response and promoted growth and metabolism depending on the gut microbiota. Conclusions These results indicated the mechanism of probiotic action of B. licheniformis H2 in maintaining intestinal health and thus promoting growth and B. licheniformis H2 may serve as an antibiotic substitute to prevent subclinical necrotic enteritis in poultry farming.